An Analysis of Educational Value in Moana Movie - Widha Adriana; Ari Fajria Novari; Tatu Munawaroh (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to analyze the educational values and core character traits represented in the animated film Moana. The research focuses on two main questions: (1) what types of educational values are portrayed in the film, and (2) how the main characters embody key character traits. A qualitative descriptive method was employed, involving repeated viewing of the film and analysis of its transcript using two theoretical frameworks: the 18 national character values proposed by Zaqiah and Rusdiana (2014), and the Character Education Framework by the Indonesian Ministry of Education and Culture (2017).The findings revealed that 16 out of 18 national character values were present in the film, including values such as responsibility, independence, social care, honesty, and religious commitment. However, tolerance and love for reading were not identified. In addition, the character analysis showed that the main character, Moana, consistently exemplifies the five core character values outlined by the Ministry: religiosity, nationalism, independence, mutual cooperation, and integrity. These results suggest that Moana serves not only as a source of entertainment but also as an effective medium for character education, especially for young learners. The film has the potential to be used as a supporting material in educational settings to promote national character development through engaging and meaningful content.